Medicament Comprising Donepezil and Carbostyril Derivative for Alzheimer Treatment - Singh, Jyoti; Sharma, Shaveta (International Journal of Psychosocial Rehabilitation, 2019)
Donepezil is the predominant Alzheimer’s drug in over fifty countries. The Donepezil is a strongly active and reversible piperidine derivative with AChEI activity that has the largest pharmacological benefit for cognitive recovery and reaction risk (40% –58%), side effects (6.0 % –13.0 %) and side effects (5.0% –13.0%) in comparison to AD compared with traditional acetylcholinesterase inhibitors (AChEI). Although donepezil is an inexpensive treatment, most research indicate that this drug can provide mild to extreme DA with a mild, slower development of disease and a reduced institutionalization of attitude, cognition and daily life. This is a modest advantage. Donepezil will also be helpful for people with vascular dementia in the same manner as AD. This paper aims at presenting a medication that includes donepezil and carbostyril derivatives, or even salt, to cure Alzheimer’s with impressive synergistic methods to combat the disease of Alzheimer.